Toxicity study of ochratoxin A using HEK293 and HepG2 cell lines based on microRNA profiling - Zhao, Junyi; Dweep, Harsh; Gretz, Norbert (Human and experimental toxicology, 2017)
Ochratoxin A (OTA) induced DNA damage, cytotoxicity, and apoptosis in mammalian cell lines. Micro RNAs (miRNAs) are involved in physiological and developmental processes and contribute to cancer development and progression. In our study, high-throughput miRNA profiling and Kyoto Encyclopedia of Genes and Genomes analysis were applied to comparatively study the toxicity of OTA in HEK293 cells and HepG2 cells treated with 25 μM OTA for 24 h. In these two cells, the same changing miRNAs were mostly related to signal transduction pathways, whereas the different changing miRNAs were mostly related to human cancer pathways. DGCR8, Dicer1, and Drosha were significantly suppressed in HEK293 cells, indicating an impairment of miRNA biogenesis. The damage seemed more extensive in HEK293 cells. Cell models and in vivo models were also compared. Many miRNAs in vitro were markedly different from those in vivo; however, OTA toxicity was observed both in vitro and in vivo. The classification of deregulated pathways is similar. The biogenesis of miRNA was impaired in both lines. In conclusion, deregulated miRNAs in vitro are mostly related to human cancer and signal transduction pathways. The deregulated pathways in vivo are similar to those in vitro.